Persepsi Guru dan Siswa Terhadap Penggunaan Absensi Barcode Berbasis Google Spreadsheet di SDN 28 Kota Jambi - Pratiwi, Asih; Sabbihisma, Septa; Anwary, Nurlis; Salwa Hilmana, Arisma; Aqua Muthariq, Muhammad; Syarif, Ahmad; Kuntarto, Eko; Destrinelli; Sofyan, Hendra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the development of digital technology in educational administration, particularly the use of barcode-based attendance integrated with Google Spreadsheet in primary schools. The aim of this research is to describe the implementation of the barcode attendance system and to explore teachers’ and students’ perceptions of its use at SDN 28 Kota Jambi. This study employs a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving teachers and students who directly use the system. The research subjects consisted of teachers and students who were directly involved in the use of the attendance system. The findings show that the barcode-based attendance system using Google Spreadsheet improves the effectiveness and efficiency of attendance management, and simplifies the recording and storage of attendance data in digital form. Teachers and students responded positively, as the system is considered practical and easy to use. However, several challenges were identified, such as limited internet access, inadequate supporting devices, and users’ digital literacy. Therefore, adequate infrastructure support and training are needed to optimize and sustain the implementation of the barcode attendance system.